Health Status of Women in Tondo Permanent Residence: Metabolic Syndrome and Quality of Life - Faisal, T. Iskandar; Nurmiaty, Nurmiaty; Orno, Theosobia Grace; Kurniawan, Rahmat (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Natural disasters result in increased risk of metabolic syndrome (MetS) and reduced quality of life (QoL), especially in vulnerable groups such as women. Objective: To determine the relationship between the incidence of metabolic syndrome and the quality of life of women in Tondo Permanent Residence, Palu City. The study used a cross sectional design with a total sample of 80 women aged 18-65 years selected by purposive sampling. Data were collected through measurement of blood pressure, lipid profile, blood glucose, abdominal circumference, and quality of life questionnaire, then analyzed using chi square test and odds ratio (OR) with STATA software.  53.75% of respondents had metabolic syndrome, with significant risk factors including age, high blood pressure, total cholesterol >200 mg/dL, triglycerides >200 mg/dL, blood glucose >100 mg/dL, and abdominal circumference >80 cm. Abdominal circumference >80 cm was the strongest predictor with an OR of 77.5. Women with a better metabolic profile had a higher quality of life. There is a significant association between metabolic syndrome and the quality of life of women in Tondo Permanent Residence.